Analisis Kandungan Hidrokuinon dalam Krim Wajah yang Beredar di Klinik Kecantikan di Kota Mataram - Irmatika Hendriyani; Baiq Nurabety; Yuli Fitriana; Eva Tri Apriani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Facial creams are cosmetics made up of chemicals and other materials that can pale black spots (brown) on the skin. Hydroquinone is an additive in whitening cream, and hydroquinone is an active ingredient that can control the production of uneven pigments, more to reduce or inhibit the formation of melanin.Use of hydroquinone in cosmetics, especially facial creams should not be more than 2% .The excessive use of hydroquinone can cause ocronisis, such as rough blue-gray skin.This study aims to determine whether there are hydroquinone compounds in facial creams circulating at the Beauty Clinic in Mataram City.If hydroquinone is found, further testing is done to uk determines how much content of hydroquinone in the face cream. This study describes the presence or absence of hydroquinone in the face cream and wants to know the amount of hydroquinone in the face cream. The method used in this study was a color reaction test reacted by feCl3, Benedict and AgCo3 reagents, and Serimetric Titration Test used for Titration with Serium (IV) Sulfate 0.01N. From the research with color reaction test showed 4 positive samples containing hydroquinone compounds, and 3 samples that had a high amount of hydroquinone in face cream did not meet the requirements of> 2%. Key word:CosmeticsFacial creamHidroquinonQualitative analysisQuantitative analysis